Reference equations for harmonizing gait speed results of different test protocols in community-dwelling older adults - Lindemann, Ulrich; Krumpoch, Sebastian; Freiberger, Ellen; Klenk, Jochen (Aging Clinical and Experimental Research, 2022)
Background and aims Different gait speed assessment protocols regarding start and stop of walking make comparison between studies impossible. The aim of this study was providing reference equations to estimate a person & PRIME;s steady-state gait speed from gait speed measured with a test protocol including static start and/or stop.Methods Gait speed of 150 community-dwelling older adults (mean age 80.5 & PLUSMN; 4.5 years; 61% women) was measured over 4 m with different assessment protocols regarding start and stop of walking on an instrumented walkway. Reference equations to estimate steady-state gait speed from the results of other test protocols were calculated by regression analysis within a fivefold cross-validation.Results Mean absolute errors and the root mean squared errors of all reference equations ranged from 0.063 m/s to 0.074 m/s and 0.082 m/s to 0.096 m/s, respectively.Conclusions The provided reference equations can help harmonizing results between studies in community-dwelling older adults.
CRIS-Team WoS Importer:2023-01-27